The problem of the handicapped between marginalisation and integration: sociological reflections on the subject - Burgalassi, Silvano (Medicina e Morale, 2024)
It is not difficult to note that in tandem with the refinement of collective awareness and consciousness, phenomena typical of our age, albeit one steeped in contradictions, the problem of the handicapped is gradually being re-proposed to public opinion from an exclusively biological-individual setting to a conspicuous opening up to the sphere of the social and public sphere.